HUBUNGAN KECEMASAN DAN PENGETAHUAN PENGGUNAAN OBAT DENGAN KEPATUHAN MINUM OBAT PENDERITA HIPERTENSI - Pisca Valentina Cristin; Ida Effendi (Fakultas Kedokteran Universitas Trisakti, 2025)
Background: Hypertension is a major cause of cardiovascular disease and premature death worldwide. Compliance with hypertension treatment plays an important role because it is long term process to control the blood pressure. This study aims to see whether anxiety and knowledge of drug use can affect medication adherence in patients with hypertension. Methods: This study was an analytic observational design with a cross-sectional approach. The sample was patients with hypertension who visited Grogol Health Center. The sample selection technique was consecutive non-random sampling. Data were obtained through interviews and questionnaire. Anxiety variable data was obtained through the Hamilton Anxiety Rating Scale (HARS) questionnaire, the knowledge variable was obtained through a drug use knowledge questionnaire and the medication adherence variable was obtained through the Morisky Medication Adherence Scale (MMAS) questionnaire . Data obtained were analyzed using the Chi-square test and Fisher's exact. Results: Study on the relationship between anxiety and knowledge of drug use with drug compliance in hypertension was conducted on 134 respondents showing a value of p=0.986 and p=0.403. Conclusion: There was no significant relationship between anxiety and knowledge of drug use with antihypertensive drug compliance in patients with hypertension at Grogol Community Health Center.